Dynamic Changes of Gene Expression in Mouse Mural Trophectoderm Regulated by Cdx2 During Implantation - Suzuki, Daisuke; Sasaki, Keisuke; Kumamoto, Soichiro; Tanaka, Keisuke; Ogawa, Hidehiko (Frontiers in Cell and Developmental Biology, 2022)
Implantation of the blastocyst into the uterus is a specific and essential process for mammalian embryonic development. In mice, implantation is initiated from the mural trophectoderm (mTE) of the blastocyst and the mTE controls implantation progression by acquiring the ability to attach and invade into the endometrium while differentiating into primary trophoblast giant cells. Nevertheless, it remains largely unclear when and how the mTE differentiates and acquires this ability during implantation. Here, by RNA sequencing analysis with the pre- and peri-implantation mTE, we show that the mTE undergoes stage-specific and dynamic changes of gene expression during implantation. We also reveal that the mTE begins down-regulating Cdx2 and up-regulating differentiation marker genes during the peri-implantation stage. In addition, using trophectoderm (TE) -specific lentiviral vector-mediated gene transduction, we demonstrate that TE-specific Cdx2 overexpression represses differentiation of the mTE into the primary trophoblast giant cells. Moreover, we reveal that TE-specific Cdx2 overexpression also represses the up-regulation of cell adhesion- and migration-related genes, including Slc6a14, Slc16a3, Itga7, Itgav and Itgb3, which are known to regulate migration of TE cells. In particular, the expression of Itgb3, an integrin subunit gene, exhibits high inverse correlation with that of Cdx2 in the TE. Reflecting the down-regulation of the genes for TE migration, TE-specific Cdx2 overexpression causes suppression of the blastocyst outgrowth in vitro and abnormal progression of implantation in vivo. Thus, our results specify the time-course changes of global gene expression in the mTE during implantation and uncover the significance of Cdx2 down-regulation for implantation progression.